Spatial and temporal variability in the R-5 infiltration data set: Deja vu and rainfall-runoff simulations - Loague, Keith; Kyriakidis, Phaedon (My University, 1997)
This paper is a continuation of the event-based rainfall-runoff model evaluation study reported by Loague and Freeze [1985]. Here we reevaluate the performance of a quasi-physically based rainfall-runoff model for three large events from the well-known R-5 catchment. Five different statistical criteria are used to quantitatively judge model performance. Temporal variability in the large R-5 infiltration data set [Loague and Gander, 1990] is filtered by working in terms of permeability. The transformed data set is reanalyzed via geostatistical methods to model the spatial distribution of permeability across the R-5 catchment. We present new estimates of the spatial distribution of infiltration that are in turn used in our rainfall-runoff simulations with the Horton rainfall-runoff model. The new rainfall-runoff simulations, complicated by reinfiltration impacts at the smaller scales of characterization, indicate that the near-surface hydrologic response of the R-5 catchment is most probably dominated by a combination of the Horton and Dunne overland flow mechanisms.
Keywords: Groundwater flow; Catchments; Hydrologic model